THE ROLE OF ISLAMIC LAW IN REGULATING CRYPTOCURRENCY AND BLOCKCHAIN TECHNOLOGY: A CASE STUDY OF INDONESIA’S REGULATORY FRAMEWORK - Marloni Anggita; Bilal Aslam; Sara Hussain (Yayasan Adra Karima Hubbi, 2025)
significant legal and ethical questions, particularly in Muslim-majority countries like Indonesia, where Islamic law (Shariah) plays a central role in financial regulation. This study examines the role of Islamic law in regulating cryptocurrency and blockchain technology, focusing on Indonesia’s regulatory framework. The research aims to assess the compatibility of these technologies with Shariah principles and identify gaps in the current regulatory approach. By doing so, it seeks to provide recommendations for developing a Shariah-compliant regulatory framework that balances innovation with ethical and legal considerations. Using a mixed-methods approach, this study combines legal analysis of Indonesia’s regulatory framework with qualitative interviews with Islamic scholars, regulators, and industry experts. Data were analyzed to evaluate the alignment of cryptocurrency and blockchain technology with Shariah principles, such as the prohibition of riba (interest) and gharar (uncertainty). The findings reveal that while blockchain technology has potential applications in Islamic finance, cryptocurrencies face significant challenges due to concerns over volatility, speculation, and lack of intrinsic value. The study concludes that Indonesia’s regulatory framework must be adapted to address the unique challenges posed by cryptocurrency and blockchain technology while ensuring compliance with Shariah principles.